Proteus syndrome with late diagnosis confirmation: a case report - Dockienė, Ilona; Čiuplinskas, Martynas; Zagorskis, Rimantas; Kontrimavičiūtė, Eglė (Frontiers in Pediatrics, 2025)
Proteus syndrome (PS) is a rare, highly polymorphous and complex disorder characterized by assymetric and/or disproportional overgrowth of limbs, hamartomas and vascular deformations. Typically, the first signs of PS appear between 6 and 18 months of age, are subtle and might be overlooked. We report a case of a 17 year old boy which was first diagnozed with PS after left limb amputation in 2021 (age of 14), though retrospectively the first signs of left hand enlargement appeared at 18 months. At the age of 3 years vascular surgery of venous malformation on his left leg was performed, molecular genetic tests from blood revealed no abnormalities. At the time Klipper-Trenaunay syndrome was diagnosed according to clinical criteria. In 2021 whole exome sequencing (WES) confirmed the diagnosis of PS after the test of affected tissues after amputation. We review the role of multidisciplinary approach implicating different physicians, role of radiologist with the multiple findings in this rare pathology with high variability of clinical presentation. Considering the complications and early mortality (up to 27 years old) observed in patients we emphasizet he significance of early suspicion and diagnosis of PS and the need for symptomatic multidisciplinary team follow-up which aims to minimize the degree of disability, prophylaxis of thrombembolic events and improve quality of life.